2009
DOI: 10.1007/s10661-009-1213-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic deposit (leonardite) on degradation of semi-volatile and heavy hydrocarbons and soil quality in crude-oil-contaminated soil

Abstract: In order to investigate the bioremedial potential of humic deposit (leonardite), the effects of the treatments of leonardite and a commercial bioaugmentation agent on the degradation of a variety of petroleum hydrocarbons (C13-C31) and soil enzyme activities (urease acid-alkaline phosphatase and dehydrogenase) were tested within a soil incubation experiment lasting 120 days. Experimentally crude-oil-contaminated soil (2.5%) was regulated to a C:N:P ratio (100:15:1; Oilcon), amended with 5% of leonardite and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 68 publications
1
15
1
1
Order By: Relevance
“…The activity of soil enzymes is often used to monitor the effects of various pollutants on microbial functioning (Turgay et al 2010, Tang et al 2014, Tomkiel et al 2015. In the tested soils, the activities of a range of enzymes contributing to the biogeochemical cycle of carbon, nitrogen and phosphorus were determined (Fig.…”
Section: Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of soil enzymes is often used to monitor the effects of various pollutants on microbial functioning (Turgay et al 2010, Tang et al 2014, Tomkiel et al 2015. In the tested soils, the activities of a range of enzymes contributing to the biogeochemical cycle of carbon, nitrogen and phosphorus were determined (Fig.…”
Section: Enzyme Activitymentioning
confidence: 99%
“…Several studies have demonstrated that DHA is among the most sensitive parameters for evaluation of hydrocarbons toxicity and stress (Irha et al 2003, Gianfreda et al 2005. Turgay et al (2010) observed that the decrease in the content of hydrocarbons resulted in an increase of DHA over time during the bioremediation process of soil contaminated with petroleum hydrocarbons. However, Tang et al (2012) examining the bioavailability of petroleum hydrocarbons under different attenuation conditions noticed an increase in DHA immediately after the contamination of soil and its decline with the duration of the experiment.…”
Section: Enzyme Activitymentioning
confidence: 99%
“…Phosphatase activity (PA) is important to soil P cycling. PA is sensitive to environmental perturbations and might therefore be a suitable selection for inclusion in the soil quality index (Turgay et al, 2010). This study clearly demonstrated the application of wastewater sludge in biodegradation of TPH by native microbial consortium not only as biostimulant, but also as inducers of degrader enzymes released by the microorganisms.…”
Section: Soil Enzyme Activitiesmentioning
confidence: 59%
“…Turgay et al, (2010) reported that some enzymes, including phosphatase, are involved in N and P cycling and might not directly influence hydrocarbon presence.…”
Section: Soil Enzyme Activitiesmentioning
confidence: 99%
“…Thus, it would come to a burning question to treat the oil-polluted soil to recovery level in a short period (Turgay et al, 2010). The bioremediation technology could be adopted because of its low cost, pollution-free, and high efficient characters.…”
Section: Introductionmentioning
confidence: 99%